TINGKATKAN PEMBERDAYAAN IBU-IBU PKK DESA TOKET LEWAT INOVASI PEMANFAATAN LIMBAH TAHU - nailurrahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Toket Village is part of Proppo District where the livelihood is producing tofu. Tofu dregs waste is waste produced from the tofu making process that is no longer used. In the tofu making process, unused tofu waste extract is often traded at a low price as animal feed. In fact, tofu dregs still have a protein content of 8.66%; fat 3.79%. With proper utilization, tofu dregs waste can have economic value that can improve the welfare of local MSMEs. This KKN is trying to innovate the making of tofu dregs into snacks in the form of 'snacks' which are packaged in the form of community service by involving PKK mothers in Toket Village, Proppo District. This community service activity is carried out by providing education that tofu dregs also have a higher economic value and the practice of making it is quite easy and simple with basic ingredients that are easy to find. The hope of this training is to educate the community as an effort to utilize tofu dregs waste with economic value.